2017
DOI: 10.3389/fvets.2017.00118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strategies to Control a Potential Outbreak of Foot-and-Mouth Disease in Sweden

Abstract: To minimize the potential consequences of an introduction of foot-and-mouth disease (FMD) in Europe, European Union (EU) member states are required to present a contingency plan. This study used a simulation model to study potential outbreak scenarios in Sweden and evaluate the best control strategies. The model was informed by the Swedish livestock structure using herd information from cattle, pig, and small ruminant holdings in the country. The contact structure was based on animal movement data and studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…For example, poliovirus is infective at pH values of 3.0, while FMDV is labile below pH values of 6.0 (Racaniello, 2013). Additionally, while both, poliovirus and FMDV have been shown to persist longer when the virus was inoculated onto a faecal media, and conditions in TA B L E 1 This table provides references by grouping for current models used for strategic policy development and studies that were either removed from further analysis or included for the full statistical analysis References Group # of Studies (Andel, 2018;Dórea, Nöremark, Widgren, & Frössling, 2017;East et al, 2016;Gale et al, 2015;Garner & Beckett, 2005;Harvey et al, 2007;Hayama, Yamamoto, Kobayashi, Muroga, & Tsutsui, 2013;Keeling et al, 2001;SANSON et al, 2011;Stevenson et al, 2013;Tildesley & Ryan, 2012;Traulsen, Rave, Teuffert, & Krieter, 2011) Current Policy Models - (Barlow, 1972;Barlow & Donaldson, 1973;Donaldson, 1972;Donaldson & Ferris, 1975) Removed 4 (Alexandersen et al, 2002;Bedson et al, 1927;Bøtner & Belsham, 2012;Donaldson et al, 1970;Eisner & McVicar, 1980;Grzitdnov, 1957;Hyslop, 1965;Kindiakov, 1960;McColl et al, 1995;Nauryzbaev, 1966;Olitsky et al, 1928;Pacheco et al, 2017;Rozov, 1966;Sellers & Parker, 1969;Shil'nikov, 1959;Wagener, 1928) Included 16…”
Section: The Influence Of Environmental Factors On Viral Survivalmentioning
confidence: 99%
“…For example, poliovirus is infective at pH values of 3.0, while FMDV is labile below pH values of 6.0 (Racaniello, 2013). Additionally, while both, poliovirus and FMDV have been shown to persist longer when the virus was inoculated onto a faecal media, and conditions in TA B L E 1 This table provides references by grouping for current models used for strategic policy development and studies that were either removed from further analysis or included for the full statistical analysis References Group # of Studies (Andel, 2018;Dórea, Nöremark, Widgren, & Frössling, 2017;East et al, 2016;Gale et al, 2015;Garner & Beckett, 2005;Harvey et al, 2007;Hayama, Yamamoto, Kobayashi, Muroga, & Tsutsui, 2013;Keeling et al, 2001;SANSON et al, 2011;Stevenson et al, 2013;Tildesley & Ryan, 2012;Traulsen, Rave, Teuffert, & Krieter, 2011) Current Policy Models - (Barlow, 1972;Barlow & Donaldson, 1973;Donaldson, 1972;Donaldson & Ferris, 1975) Removed 4 (Alexandersen et al, 2002;Bedson et al, 1927;Bøtner & Belsham, 2012;Donaldson et al, 1970;Eisner & McVicar, 1980;Grzitdnov, 1957;Hyslop, 1965;Kindiakov, 1960;McColl et al, 1995;Nauryzbaev, 1966;Olitsky et al, 1928;Pacheco et al, 2017;Rozov, 1966;Sellers & Parker, 1969;Shil'nikov, 1959;Wagener, 1928) Included 16…”
Section: The Influence Of Environmental Factors On Viral Survivalmentioning
confidence: 99%
“…Bate et al [ 7 ] simulated FMD transmission in a three-county area in California, demonstrating the effectiveness of preemptive culling of highest-risk herds and ring vaccination. This model was widely used and later adapted to analyze FMD mitigation strategies in other countries, including Sweden [ 21 ] and Denmark [ 11 ]. Other stochastic, state-transition simulation models included the NAADSM [ 22 ], AusSpread [ 23 ], InterSpreadPlus [ 24 ], and AADIS [ 25 ], which involve multiple animal species and pathways for disease spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Pendell et al estimated a loss of 18 around $16-140 billion for an outbreak in the Midwestern U.S. originating from the 19 proposed National Bio and Agri-Defense Facility in Kansas [13]. 20 Liu et al [6] presented a spatially explicit agent-based simulator for synthesizing 21 beef cattle movements, and provided insight into the influence of network dynamics on 22 epidemic dynamics. It was shown that the new infections were driven by the trading 23 behavior, and that the removing rate determined whether the virus could survive long 24 enough to infect others.…”
mentioning
confidence: 99%
“…The parameters used in this model are specified as follow: infectious rate for direct 107 contact β dir = 0.95day −1 calf −1 [20],λ = 1/3.59day −1 [21] which means that the 108 average incubation time is 3.59 days. For the infection rate of indirect contact β ind , we 109 use β ind = 0.1day −1 calf −1 for the base scenario, since no specific value is available in the literature.…”
mentioning
confidence: 99%